USE OF SECONDARY HEAT FOR DECREASE IN ELECTRICITY CONSUMPTION IN THE COURSE OF BURIROVANIYA OF THE WIRE - E. V. Chebotaryov (Литьë и металлургия)
In article introduction of an energy saving activity in technological process of wire’s surfacing by borate of soda during drawing is described. This activity is directed to decrease in electricity consumption for heating of solution in borate of soda bathtubs by use of the recovered heat of steel-smelting shops and is described in the article.